Cable force optimization of a curved cable-stayed bridge with combined simulated annealing method and cubic B-Spline interpolation curves. (15th December 2019) - Guo, Junjun; Yuan, Wancheng; Dang, Xinzhi; Alam, M. Shahria
Highlights: Smooth cable force distribution in a cable-stayed bridge can be represented by a cubic B-Spline interpolation curve. A number of reasonable local minima of the objective function can be generated for the proposed method. The optimum solution can be selected as the minimum of the generated local minima. The proposed method of determining the optimum cable forces can be easily implemented in practice. Abstract: Cable-stayed bridges have been extensively constructed in China in the recent two decades. This type of bridge is characterized by flexible cables that transfer the deck loads to pylons. This study focuses on the cable force optimization of a curved cable-stayed bridge based on the proposed method where simulated annealing and cubic B-Spline interpolation curves are combined for the optimization. Firstly, the numerical model of a curved cable-stayed bridge is generated in OpenSees platform. Secondly, the proposed method is elaborately described, including the establishment of cubic B-Spline interpolation curves based on four interpolation points, the flow chart of simulated annealing algorithm, objective function, design variables, and design load cases. Finally, the static responses of the bridge deck, pylons, and cables are calculated and discussed under the obtained optimum cable forces. The results reveal that the currently proposed method can efficiently generate a number of values for the objective function, and the optimum solution can be selected as the minimum of the generated objective function values. In addition, cable forces obtained by the proposed method change gradually. The proposed method for determining the optimum cable forces can be easily implemented in practice.